2021
DOI: 10.1186/s43591-021-00015-x
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to microplastic fibers does not change fish early life stage development of three-spined sticklebacks (Gasterosteus aculeatus)

Abstract: Microplastic fibers are frequent contaminants of aquatic ecosystems. Early life stages of aquatic organisms are predicted to be especially vulnerable to microplastic pollution. We hypothesized that microplastic fibers in the water column might interfere with fertilization and embryonic development of fish. We tested this with an in vitro fertilization system with three-spined sticklebacks. Six egg clutches were divided and one half was fertilized and bread out in water with polyester fibers (PET fibers; mean d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…Additionally, several investigations revealed that MPs had little impact on the development of fertilized eggs. 31,32 Additionally, 33 discovered that low levels of polystyrene MPs reduce marine medaka's early developmental toxicity to phenanthrene (Oryzias melastigma). To the best of our knowledge, the metabolic reactions to MPs from marine bivalves varied depending on the MPs' characteristics (including kind, shape, and size), as well as the exposure modes (including length and abundance).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, several investigations revealed that MPs had little impact on the development of fertilized eggs. 31,32 Additionally, 33 discovered that low levels of polystyrene MPs reduce marine medaka's early developmental toxicity to phenanthrene (Oryzias melastigma). To the best of our knowledge, the metabolic reactions to MPs from marine bivalves varied depending on the MPs' characteristics (including kind, shape, and size), as well as the exposure modes (including length and abundance).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is important that researchers have the flexibility to select specific microplastic types for their experiments. Additionally, many previous studies coated microplastics in a thin layer of surfactant to achieve a homogenous distribution of particles in solution [46][47][48] . Surfactants can have toxic effects on aquatic organisms 49,50 and may also increase the proliferation of bacterial growth on the surface of microplastics 51 .…”
mentioning
confidence: 99%